Threat appraisal and prevention of risky sexual behavior among high school students in Indonesian: the mediating roles of response efficacy and self-efficacy - Erni Gustina; Ira Nurmala; Nunik Puspitasari (Institute of Advanced Engineering and Science, 2026)
Premarital sexual behavior among adolescents remains a public health concern. However, school programs often focus on risk perception without showing how perceived threat can lead to protection. This study examined the influence of threat appraisal (severity and vulnerability) on the prevention of premarital sexual behavior through response efficacy and self-efficacy as mediators. A cross-sectional survey was conducted among 333 high school students selected by multistage sampling. Likert-scale measures assessed severity, vulnerability, response efficacy, and self-efficacy. The model was analyzed using partial least squares structural equation modeling (PLS-SEM) with bootstrapping (α=0.05). Most participants reported no premarital sexual behavior (66.1%). Severity and vulnerability positively predicted response efficacy and self-efficacy, with severity exerting a stronger effect. Response efficacy and self-efficacy were negatively linked to premarital sexual behavior (p<0.05), meaning that higher coping appraisal (the ability to handle risky situations) was associated to lower risk behavior. Indirect effects from severity and vulnerability to behavior through both mediators were significant. The model explained 34% of the variance in premarital sexual behavior. Threat appraisal reduced premarital sexual behavior mostly by improving coping appraisal. Thus, school-based interventions should combine risk communication with the development of refusal, negotiation, and self-confidence skills to support protection.